Proactive behaviour as a mediator of the relationship between career management and career satisfaction - Azman Ismail,; Wan Aishah Wan Mohd Nowalid,; Rizal Abu Bakar, (Penerbit Universiti Kebangsaan Malaysia, 2016)
This study aims to quantify the relationship between career management, proactive behaviour and career satisfaction. A survey method was employed to gather self-report questionnaires from employees who work at a state Islamic agency in Peninsular Malaysia. The outcomes of the SmartPLS path model analysis showed two important findings. First, the relationship between job autonomy and proactive behaviour was positively and significantly correlated with career satisfaction. Second, the relationship between transformational leadership and proactive behaviour was positively and significantly correlated with career satisfaction. This finding confirms that proactive behaviour does act as an effective mediating variable in the relationship between career management and career satisfaction in the organizational sample. Further, this study provides discussion, implications, limitations and suggestions for future studies.